The Perceived Privacy Risk in the Modern Society (Case in Customer E-Commerce) - Hamali, Sambudi; Polim, Vincent; Yohanes, Yohanes (Bina Nusantara University, 2024)
One of the main characteristics of modern society is technological progress in everyday life, but on the other hand, challenges in modern society include the spread of fake news, disinformation, and leaks of personal data. The study's goal is to investigate the influence of social commerce information sharing (SCIS) on consumer trust and the risk of privacy perceived by consumers, as well as the effect of consumer trust on the risk of privacy perceived by Tokopedia users, as mediated through trust. A questionnaire was issued to 100 Tokopedia customers to collect data. SEM-PLS (Structural Model) with WarpPLS software version 8.0 is used for data analysis. SCIS has an effect on trust and consumer-perceived privacy risk, while trust has no effect on consumer-perceived privacy risk, according to the findings. SCIS has a higher impact on consumer trust than on their perceived privacy risks. This demonstrates the need for Tokopedia to build consumer trust.